How does an online writing for publication group promote reflective practice? Voices from two EFL lecturers (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
Reflective practice has been a prominent issue on English language teaching since it involves a deliberate action to improve one’s professional knowledge, skills, and awareness. One way to encourage reflective practice for EFL teachers is to form an online academic group. The current study examines how the discussion in an online academic writing for publication group promotes reflective thinking. This study involved two EFL teachers who participated and learned academic writing in a weekly online meeting on WhatsApp to reflect on their study. The online group discussion was recorded and coded according to the topics they talked about in the group. The topics served as a measure of critical reflectivity. Findings indicated that the EFL teachers talked over and studied academic writing in terms of how to prepare an eligible manuscript for international publication. They also discussed the problems or issues they encountered during writing a research article for publication. The issues were concerned with the research topics, writing an introduction section, difficulties in reporting the research method and procedure, and the use of academic words in their writing, to mention a few. Those issues have an implication to the difficulty in preparing an eligible manuscript and in publishing their articles This study calls for further initiations to develop reflective practice of Indonesian EFL lecturers through a series of intensive academic writing for publication purposes workshops. The foci of the workshops can address the issues on developing each section of the research article or selecting academic words suitable for writing the paper so that the process of undergoing the international publication can be less demanding.